Benefits and challenges of factors influencing the integration of blockchain technology - Florian Gottschlich (Journal of Applied Leadership and Management, 2018)
Research question: What are the benefits and challenges of critical success factors for the German logistics industry when integrating blockchain technology? Methods: A survey with six determined factors and their benefits as well as challenges was conducted to analyze the expectations of logistics professionals in Germany. Results: Cost reduction is achieved by integrating the blockchain through low marginal cost, efficient management of inventory stocks and reduced paperwork. Speed is fostered by reduced interactions and real-time exchange of information. The need of digitalization for the blockchain integration is mostly influenced by the availability of financial resources and integration of hardware components. Transparency, Complexity and Data security were not sufficiently explained.
Keywords: 650